Maximum crossrange guidance under multiple constraints for lifting body reentry vehicle - Chao, Tao; Wang, Songyan; Yang, Ming (2010 3rd International Symposium on Systems and Control in Aeronautics and Astronautics, 2010)
Maximum crossrange guidance with heat flux, overload factor and dynamic pressure constraints is required when lifting body reentry vehicle (LBRV) needs to travel long crossrange to reach the target point. A new maximum corssrange guidance method is presented for LBRV. The proposed guidance method converts maximum crossrange guidance into two subproblems, i.e. trajectory design subproblem and trajectory following subproblem, which are solved respectively. Firstly, the mathematical model of LBRV is derived taking the effects of the rotation and curvature of the earth into account, and the influence of heat flux, overload factor, dynamic pressure and terminal state constraints on the trajectory of LBRV is analyzed. After that, the trajectory design subproblem is interpreted from the aspect of optimal control. A discrete optimal control problem solution using control variables parameterization and genetic algorithm is presented, in which a new LBRV guidance control variables parameterized model is presented. Then a linear quadratic trajectory following law is proposed in order to solve the trajectory following subproblem. At last, the proposed maximum crossrange guidance method is used to design guidance law for a LBRV, and the effectiveness of the method is demonstrated through numerical simulation. It can be seen that the proposed guidance law is effective and control variable parameterized model provides some design freedom for guidance law designer.